2015
DOI: 10.1016/j.sbspro.2015.06.370
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of the Creativity of Public and Private School Teachers to their Intrinsic Motivation and the School Climate for Innovation

Abstract: Ankara University Educational Administration PhD Programme, Ankara, 06590, TurkeyThe climate for innovation is related with organizational outputs comprising the benefits of ideas, significant innovations and satisfaction of the employees and the service takers; and sophisticated applications of the effectiveness of the services as perceived by service takers. It indicates an organizational willingness necessary for experiencing innovative ideas. As for intrinsic motivation, it can be defined as the experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 33 publications
3
32
1
3
Order By: Relevance
“…Thus, intrinsic motivation can be a possible predictor of the teacher creativity in education. The same finding was established which stated that there is a constructive and medium-level association between intrinsic motivation and creativity [36]. Analysis of the relation of intrinsic motivation to creativity, though, has produced unclear findings [39].…”
Section: Intrinsic Motivation and Creativitymentioning
confidence: 70%
See 1 more Smart Citation
“…Thus, intrinsic motivation can be a possible predictor of the teacher creativity in education. The same finding was established which stated that there is a constructive and medium-level association between intrinsic motivation and creativity [36]. Analysis of the relation of intrinsic motivation to creativity, though, has produced unclear findings [39].…”
Section: Intrinsic Motivation and Creativitymentioning
confidence: 70%
“…Furthermore, several studies established that intrinsic motivation is positively related and moderately related [34][35][36]. One of the past research revealed the importance of intrinsic motivation for teachers' creativity [37].…”
Section: Problem Statementmentioning
confidence: 99%
“…from the internal aspect of the employee requires more encouragement than himself. This is, as Ryan and Deci cited in Fidan (2015), argue that intrinsic motivation is a person's inclination to discover and learn new things to improve their capacity. Individuals can act solely out of curiosity and the desire to learn without expecting rewards, or in other words do the job just to satisfy the sense of satisfaction arising out of curiosity, self-expression, and self-challenge.…”
Section: Discussionmentioning
confidence: 93%
“…In a similar way, there have been researches with a claim that schools with more flexible organizational structures in which hierarchical structures are maintained to carry out one of the main functions like coordination on one hand, and horizontal structures are allowed in order to conduct complexity absorbing functions such as communication, innovation and creativity on the other could be more successful (Fidan & Öztürk, 2015b). In these organizational structures, the following complexity absorbing strategies are found: (a) Setting different and conflicting goals at once as different sub-units have different functions, (b) undertaking various strategic activities to attain these goals, (c) decentralizing decision making processes and increasing interactions and connections within these processes.…”
Section: Reshaping Schoolsmentioning
confidence: 99%